Export of dissolved organic carbon, nitrogen and phosphorus following clear-cutting of three Norway spruce forests growing on drained peatlands in southern Finland - Nieminen, Mika (Silva Fennica, 2004)
The effect of clear-cutting on the concentrations of dissolved organic carbon (DOC), organic nitrogen (DON), NH4+, NO3â, and P in outflow water from three productive, Norway spruce dominated drained peatlands (RCC, VCC-1, VCC-2) were studied. Changes in runoff and transport loads (concentration x runoff) at two of the catchments during the frost-free period are also presented. Approximately 40% of the area was cut at RCC and VCC-2, and 72% at VCC-1. The volume removed was 250 m3 haâ1 at RCC, 259 m3 haâ1 at VCC-1, and for VCC-2, 317 m3 haâ1. The mean annual increase in outflow concentrations of DOC during the first four years after clear-cutting was 9.0 mg lâ1 at RCC, 22.8 mg lâ1 at VCC-1 and 8.4 mg lâ1 at VCC-2. Corresponding increases in the forms of nitrogen were: 0.23, 0.51 and 0.16 mg DON lâ1; 0.06, 0.31 and 0.04 mg NH4+-N lâ1; and 0.05, 0.12 and 0.22 mg NO3â-N lâ1. Clear-cutting did not significantly (p > 0.05) increase P concentrations. The increase in non-frost season runoff over the first three years after clear-cutting was 107 mm at RCC and 207 mm at VCC-1. The export loads of DOC during the non-frost season increased by 80 kg haâ1 at RCC and by 184 kg haâ1 at VCC-1 over the first three years. Corresponding increases for the other studied solutes were: 1.78 and 3.98 kg DON haâ1; 0.39 and 1.49 kg NH4+-N haâ1; 0.45 and 0.48 kg NO3â-N haâ1, and 0.09 and 0.06 kg P haâ1. The study demonstrated that clear-cutting may significantly increase the export of DOC and different forms of nitrogen from drained productive peatlands while only small increases in phosphorus export may occur.